PENGARUH INOVASI PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN TELUR ASIN DI KELURAHAN LIMBANGAN WETAN KABUPATEN BREBES - Sri Rahayu (Jurnal Strategik, 2018)
ABSTRACT The aims of this study was to find out how the effect of product innovation and price on the decision to purchase salted eggs in Limbangan Wetan Village, Brebes Regency. The research sample was 100 consumers / respondents. The analysis technique used is F test, t test and multiple linear regression analysis. Based on the results of the tests that have been carried out, the values obtained are: a. t-test for product innovation variables of 4.963 with a significance of 0.000 Ftable means that together the independent variables of product innovation and price significantly influence the purchasing decision variable. d. Regression equation Y = 10.215 + 0.434 X1 +0.276 X2 which means that the regression coefficients of product innovation variables have a dominant influence on the decision to buy salted eggs. From the results above, the product innovation variable must be a point of concern for salted egg sellers.